Effect of Irradiation in Immune Response in Rats Experimentally Affected by Giardia Lamplasia - Falak AL-Dabbagh; Zuhair Raheemo (College of Education for Pure Sciences, 2007)
Abstract The present study was carried out on white rats , Rattus rattus norvegicus infected with Giardia lamblia isolated from patients feces , to investigate the effect of radiation with gamma rays on the degree of its infection and resistance of stimulation of immune response both cellular and humoral . After 24 hrs of radiation there was a clear effect on immune response on the host as it appears that the irradiated Giardia stimulated the immune system more than those un-radiated as it stimulates the production of neutrophils , monocytes , lymphocytes .